Immigrants' settlement patterns: a methodological assessment - Emília Malcata Rebelo (2009)
This article aims to contribute to the definition and application of a methodology to support municipal decisions concerning attraction, location and distribution of immigrants in metropolitan areas. This methodology is aimed at identifying settlement patterns of specific groups of immigrants, and respective intensity, according to territorial characteristics and their own ethnic features, in relation to correspondent patterns of the whole population. It is applied, as a case study, to Oporto Metropolitan Area (Portugal). A discussion is pursued on the sociological reasons that explain the aggregation behaviours of different ethnic groups, and how those behaviours shape the morphological and typological characteristics of territorial settlements in metropolitan areas. The application of this methodology to different metropolitan areas allows (i) the monitoring of the evolution of indicators concerning immigrants and metropolitan territorial characteristics, (ii) the analysis and comparison of settlement behaviours exhibited by different ethnic groups, in relation to native correspondent behaviours (iii) the critical sketch of the evolution of the integration of different ethnic groups, and (iv) the definition and application of urban policies aimed at attracting, distributing and locating immigrants in the metropolitan areas, simultaneously assuring socio-economic territorial development and sustainability. The recent curricular revision has generated many integration meetings among the responsible professors in the main curricular areas in civil engineering education, which has engendered a strong and harmonious body of teaching/learning and research processes that embodied the strategic planning and management processes. These were internalized by the whole community (teachers, pupils, researchers, administrative staff). In this environment, the Operations Research has appeared as a new concept of curricular matter, where the evaluation processes are continuous, the individual and group capabilities are enhanced, and leadership and decision-making processes are implemented everyday. They are applied to the resolution of many concrete cases, taken from national and international firms and organizations, reporting troublesome facts they face in their current labor and productive practices. The results now begin to appear through a new generation of civil engineers that are right now entering the labor market, who are more attentive to the many different factors that interfere in decision-making, and who better faces the problems, quickly join the needed information, and take decisions more and more inclined to be the optimal decisions.